Peran Kode Etik Untuk Meningkatkan Profesionalisme Guru Pendidikan Agama Kristen - Prihanto, Joko; Pakpahan, Duma Fitri; Tarigan, Doni Pranata (Journal of Industrial Engineering & Management Research, 2022)
Teachers have a noble task to advance education that affects the development and progress of the Indonesian nation. As a profession, teachers have a code of ethics to regulate the attitudes and actions of teachers to remain professional and dignified. However, in practice there are not a few teachers who are not able to carry out their duties professionally which can be detrimental to many parties. By using a literature review research method, the author tries to describe the importance of understanding and living a code of ethics to improve teacher professionalism. The conclusion of this study is that a Christian religious education teacher must be able to apply the Indonesian teacher code of ethics with a deep awareness of God's special call to his life. Consciously improve the professionalism of teachers to expand their capacity as instruments in God's hands for His glory.